Organic Nanoparticle‐Based Fluorescent Chemosensor for Selective Switching ON and OFF of Photodynamic Therapy (PDT). Issue 20 (15th December 2016) - Gangopadhyay, Moumita; Jana, Avijit; Rajesh, Y.; Bera, Manoranjan; Biswas, Sandipan; Chowdhury, Nilanjana; Zhao, Yanli; Mandal, Mahitosh; Singh, N. D. Pradeep
Abstract: Photodynamic therapy (PDT) is a non‐invasive cancer treatment. For target‐specific PDT, targeting "overexpression" of some specific cellular markers will be highly beneficial. As Cu II content is higher in cancer cells than in normal cells, selective binding with Cu II can be the most effective mode for intracellular heterogeneity‐responsive targeted PDT. Thus, a photosensitizer showing competent PDT activity only after Cu II chelation is important for tumor‐targeted PDT. Herein, we report a new ratiometric fluorescent chemosensor based on anthracene‐N‐phenylethylenediamine nanoparticles (ANT‐pen NPs), which showed fluorescence color change from green to red upon Cu II chelation. Only the Cu II ‐bound state showed selective PDT activity; hence, this color change was used for real‐time monitoring of targeted PDT. Cellular images in cancerous HeLa and non‐cancerous NIH 3T3 cell lines showed the change in fluorescence of ANT‐pen NPs on selective binding with Cu II in HeLa cells only. MTT assay in both cells suggested massive cell destruction by ANT‐pen‐Cu II NPs only in HeLa cells upon visible light exposure, whereas NPs remained non‐toxic to NIH 3T3 cells. Abstract : Tumor‐targeted PDT under visible light activation, triggered by Cu II ‐rich environment in cancer cell has been demonstrated. Distinct fluorescent color change from green to red respectively in Cu II –bound and free form led to real‐time monitoring of PDT in vitro. Comparative MTT assay in NIH 3T3 and HeLa cell supported selective PDT in terms of greater toxicity only upon binding with excess Cu II in HeLa cells.